Association of perceived ethnic discrimination with general and abdominal obesity in ethnic minority groups: the HELIUS study. Issue 5 (13th December 2016) - Schmengler, Heiko; Ikram, Umar Z; Snijder, Marieke B; Kunst, Anton E; Agyemang, Charles
Abstract : Background: Discrimination is associated with obesity, but this may differ according to the type of obesity and ethnic group. This study examines the association of perceived ethnic discrimination (PED) with general and abdominal obesity in 5 ethnic minority groups. Methods: We used cross-sectional data from the HELIUS study, collected from 2011 to 2015. The study sample included 2297 Ghanaians, 4110 African Surinamese, 3021 South-Asian Surinamese, 3562 Turks and 3868 Moroccans aged 18–70 years residing in Amsterdam, the Netherlands. Body mass index (BMI) was used as a measure for general obesity, and waist circumference (WC) for abdominal obesity. PED was measured using the Everyday Discrimination Scale. We used linear regression models adjusted for sociodemographics, psychosocial stressors and health behaviours. In additional analysis, we used standardised variables to compare the strength of the associations. Results: In adjusted models, PED was significantly, positively associated with BMI in the South-Asian Surinamese (β coefficient 0.338; 95% CI 0.106 to 0.570), African Surinamese (0.394; 0.171 to 0.618) and Turks (0.269; 0.027 to 0.510). For WC, a similar pattern was seen: positive associations in the South-Asian Surinamese (0.759; 0.166 to 1.353), African Surinamese (0.833; 0.278 to 1.388) and Turks (0.870; 0.299 to 1.440). When stratified by sex, we found positive associations in Surinamese women, Turkish men and Moroccan men. The strength of the associations with BMI and WC was comparable in the groups. Among the Ghanaians, no significant associations were observed. Conclusions: Ethnic and sex variations are observed in the association of PED with both general and abdominal obesity. Further research on psychosocial buffers and underlying biological mechanisms might help in understanding these variations.